Effects of temperature and water saturation on the elastic moduli of sandstone and mudstone from the Lufeng geothermal field: experimental results and theoretical model. Issue 2 (24th March 2022) - Zou, Guangui; Zeng, Hu; Gong, Fei; Yin, Caiyun; Li, Shengqi; Peng, Suping; Xu, Zhengwei
SUMMARY: The key issue in the 3-D seismic exploration of geothermal reservoirs is to determine how the petrophysical properties of geothermal reservoirs change with temperature. In this paper, physical experiments on six rock samples from the Yunnan Lufeng geothermal field were used to analyse the effect of temperature on the elastic moduli of dry rock. The laboratory measurements show that under formation pressure conditions, the bulk modulus and shear modulus of the studied rock decrease linearly with increasing temperature, and the rock moduli exhibit approximately linear relationships with temperature. Gassmann's equation can be used to predict the influence of pore fluid on the P - and S -wave velocities of the rocks. To include the temperature effect in Gassmann's equation, we separately considered the rock matrix and pore fluid; we combined thermoelastic theory to introduce the influence of temperature on the rock into Gassmann's equation and directly considered the influence of temperature on the pore fluid. The effects of fluid on the physical properties of rocks were evaluated based on Gassmann's equation while considering the effect of temperature. The results show that the rock shear modulus is affected by temperature more than the bulk modulus is, which implies that the S -wave information is more sensitive to temperature. When the uniform water saturation is less than 95 per cent, temperature is the main factor influencing the rock bulk modulus. When the uniform water saturation is greater than 95 per cent, the fluid is the main factor influencing the rock bulk modulus, and the rock shear modulus is affected by only temperature. Fluid replacement with Gassmann's equation achieves results that are more consistent with laboratory measurements when the influence of temperature is considered. Gassmann's equation considering the effect of temperature reveals crucial dependences of the seismic wave velocities and elastic moduli on temperature and fluid content.